BIMBINGAN SPIRITUAL BERBASIS TERAPI LINGKUNGAN TERHADAP KORBAN NAPZA DI PANTI REHABILITASI PONDOK TETIRAH DZIKIR - Ina Ambar Wati (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2019)
AbstractThis study aims to determine the application of spiritual guidance and the significance of the research conducted by developing Islamic counseling guidance. Then the problem that will be discussed is about the methods, inhibiting factors and supporting factors of environmental-based spiritual guidance in dealing with drug patients at the PondokTetirahDzikirBerbah Rehabilitation, Sleman Yogyakarta. The method used is field research with a descriptive qualitative approach. The main data collection techniques are observation, interview, and documentary study. The results showed that spiritual therapy based on environmental therapy was applied through the Ilaahiyah approach with the Islamic Sufism of the TaradQadriyahNaqsabandiyah (TQN) method and based on environmental therapy by interacting with the community and nature. The spiritual guidance includes bathing repentance, obligatory prayers and sunnah, dzikirjahar and khofi, and fasting. While environmental therapies such as community service, participating in rice harvest events, herding goats and da'wah safaris. Inhibiting factors: facilities and infrastructure, lack of therapists and lack of assistance from the government. Supporting Factors: Motivation of the victims to recover, a cool and comfortable atmosphere of the orphanage. The results of the therapeutic method for victims of drugs can make them experience changes and return to continue their lives better. Spiritual guidance combined with a conducive and comfortable environment therapy and social interaction with the community will make patients more optimal in the healing process. Keywords: spiritual guidance, environmental therapy, drug victim, tetirah dzikir.